Respectful leadership and followers' knowledge sharing: A social mindfulness lens. (June 2020) - Gerpott, Fabiola H; Fasbender, Ulrike; Burmeister, Anne
Knowledge sharing is a discretionary act of employees who might see benefits in keeping their knowledge to themselves. We focus on the other-oriented nature of knowledge sharing to outline how respectful leadership as an other-oriented leadership style can enhance followers' knowledge sharing through its effect on followers' other-orientedness. Specifically, we propose that respectful leaders increase followers' social mindfulness—defined as the cognitive (i.e. perspective taking) and affective (i.e. empathic concern) willingness to behave in a way that increases others' opportunities—which facilitates knowledge sharing. To test our conceptual model, we conducted a three-wave field study with 275 followers, and a multi-source field study with 83 leader-follower dyads. In line with our hypotheses, followers' perspective taking (Study 1 and 2) and empathic concern (Study 1) mediated the positive effect of respectful leadership on followers' knowledge sharing. Moreover, perspective taking and empathic concern possessed interactive effects in Study 1, suggesting that the relationship between respectful leadership and followers' knowledge sharing was strongest when both components of social mindfulness were high. We discuss theoretical implications of the identified motivational pathway and elaborate on implications for practitioners who aim to facilitate knowledge sharing at work.